Hemodynamic and respiratory support in pulmonary embolism: a narrative review - Pérez-Nieto, Orlando Rubén; Gómez-Oropeza, Irene; Quintero-Leyra, Andrés; Kammar-García, Ashuin; Zamarrón-López, Éder Iván; Soto-Estrada, Maximiliano; Morgado-Villaseñor, Luis Antonio; Meza-Comparán, Héctor David (Frontiers in Medicine, 2023)
Pulmonary embolism is a common and potentially fatal disease, with a significant burden on health and survival. Right ventricular dysfunction and hemodynamic instability are considered two key determinants of mortality in pulmonary embolism, which can reach up to 65% in severe cases. Therefore, timely diagnosis and management are of paramount importance to ensure the best quality of care. However, hemodynamic and respiratory support, both major constituents of management in pulmonary embolism, associated with cardiogenic shock or cardiac arrest, have been given little attention in recent years, in favor of other novel advances such as systemic thrombolysis or direct oral anticoagulants. Moreover, it has been implied that current recommendations regarding this supportive care lack enough robustness, further complicating the problem. In this review, we critically discuss and summarize the current literature concerning the hemodynamic and respiratory support in pulmonary embolism, including fluid therapy, diuretics, pharmacological support with vasopressors, inotropes and vasodilators, oxygen therapy and ventilation, and mechanical circulatory support with veno-arterial extracorporeal membrane oxygenation and right ventricular assist devices, while also providing some insights into contemporary research gaps.